Modified Instructional Teaching Method - Luís Manoe (Newinera Publisher, 2020)
Competency-based Language Teaching (CBLT) causes character education issue and its competence in facing a complex social circumstance which is quite conspicuous when implementing in national scale. Content-based Instruction (CBI) covers students and teacher proficiency that is considered not effective if the implementation does not take material and students’ different competence into account. Cooperative Language Learning (CLL) weakness shows a feasible challenging with the classroom discussion dynamics and the allotted time. The weakness shows one leads to a broad scale, the other one causes teacher and students and the last costs the practical implementation.